L’alternance codique dans le rap algérien et tunisien - Felix Wiedemann (L’Année du Maghreb)
Hip-hop culture in general and especially rap music are important ways of expression for urban Algerian and Tunisian youths. Hence rappers use their songs to speak of everyday life and to address personal and socio-political problems. Their lyrics are written in a multitude of languages, mirroring multilingualism and diglossia in the Maghreb. This article examines how the Algerian rapper Lotfi Double Kanon and the Tunisian rapper Balti make use of Arabic, French and English in their songs. It is first analyzed how linguistic conventions limit and structure code-switching from one language to the other. These conventions can also be found in everyday speech and are expressed by the Matrix Language Frame Model. Finally it is explored how the rappers use code-switching within the frame of these limitations in order to enhance their means of artistic expression.